Effect of muscle energy technique and static stretching on pain and functional disability in patients with mechanical neck pain: A randomized controlled trial - Apoorva Phadke, MPT; Nilima Bedekar, PhD; Ashok Shyam, MS (Ortho); Parag Sancheti, MS (Ortho) (Hong Kong Physiotherapy Journal, 2016)
Background: Mechanical neck pain is one of the common musculoskeletal disorders. Muscle energy technique (MET) may be a useful intervention for treating such disorder. Objective: The aim of this study was to compare the effect of MET with passive stretching on pain and functional disability in people with mechanical neck pain. Methods: A randomized controlled trial was undertaken. Sixty patients with mechanical neck pain were randomly allocated to either the MET group or control group. The former group received MET, and the latter group received static stretching. Both groups received conventional therapy. Treatment was given once a day for 6 days. A visual analogue scale (VAS) was used to measure the intensity of pain, and functional disability was assessed using the neck disability index (NDI) was immediately before treatment and again on the 6th day. Results: VAS and NDI scores showed a significant improvement in both MET and stretching groups on the 6th day postintervention (p < 0.05). However, both VAS and NDI scores showed better improvement in the MET group as compared to the stretching group (p < 0.025). Conclusion: Muscle energy technique was better than stretching technique in improving pain and functional disability in people with mechanical neck pain.